2003
DOI: 10.4269/ajtmh.2003.68.586
|View full text |Cite
|
Sign up to set email alerts
|

Dihydrofolate Reductase and Dihydropteroate Synthase Genotypes Associated With in Vitro Resistance of Plasmodium Falciparum to Pyrimethamine, Trimethoprim, Sulfadoxine, and Sulfamethoxazole

Abstract: Abstract. A total of 70 Plasmodium falciparum isolates were tested in vitro against pyrimethamine (PYR), trimethoprim (TRM), sulfadoxine (SDX), and sulfamethoxazole (SMX), and their dihydrofolate reductase (dhfr) and dihydropteroate synthase (dhps) genotypes were determined. dhfr genotypes correlated with PYR and TRM drug responses (r ‫ס‬ 0.93 and 0.85). Isolates with wild-type alleles showed mean half inhibitory concentrations (IC 50 ± SD) of 0.10 ± 0.10 and 0.15 ± 0.06 g/100 l for PYR and TRM. Parasites with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(36 citation statements)
references
References 23 publications
2
33
1
Order By: Relevance
“…Also for WR99210, the IC 50 of 0.039 nM was very near to those previously reported for different parasite lines (0.075-0.21 nM) [45][46][47]. Trimethoprim IC 50 concentrations that have been reported to range from 130 nM to 30 lM in different assay types of chloroquine sensitive and resistant strains in medium depleted of folic acid and pABA are in harmony with our observation (1.2 lM) [47][48][49]. For methotrexate, sensitivity reports range between 0.32 nM and 600 nM in in vitro assays, which is in agreement with our NF54 IC 50 measurement of 190 nM [50][51][52].…”
Section: Discussionsupporting
confidence: 92%
“…Also for WR99210, the IC 50 of 0.039 nM was very near to those previously reported for different parasite lines (0.075-0.21 nM) [45][46][47]. Trimethoprim IC 50 concentrations that have been reported to range from 130 nM to 30 lM in different assay types of chloroquine sensitive and resistant strains in medium depleted of folic acid and pABA are in harmony with our observation (1.2 lM) [47][48][49]. For methotrexate, sensitivity reports range between 0.32 nM and 600 nM in in vitro assays, which is in agreement with our NF54 IC 50 measurement of 190 nM [50][51][52].…”
Section: Discussionsupporting
confidence: 92%
“…Homology modeling predicts that trimethoprim would be less affected than pyrimethamine by mutation at DHFR codon 108 (Warhurst, 2002), but is unclear on the effect on trimethoprim of further mutations at 51 and 59 in combination with S108N or S108. The unusual finding by Jelinek, which could have implications for malaria control and for trimethoprim-sulfamethoxazole prophylaxis against opportunistic infections in human immunodeficiency virus-infected persons in Africa where sulfadoxine-pyrimethamine is used, was not supported by later in vitro experiments using recombinant yeast expressing the novel serine-108/N51I/C59R allele (Iyer et al, 2001) and P. falciparum isolates with known dhfr mutations (Khalil et al, 2003). In these studies, as had been previously reported (Winstanley et al, 1995), there was significant in vitro cross-resistance between pyrimethamine and trimethoprim.…”
Section: The Move To Field Isolatesmentioning
confidence: 96%
“…Cotrimoxazole (CTX [trimethoprim-sulfamethoxazole]) is a drug used to treat acute respiratory infections, and cross-resistance between trimethoprim, a component of CTX, and pyrimethamine has been demonstrated in vitro (10,11). Similarly, cross-resistance between sulfamethoxazole and sulfadoxine has also been demonstrated (10).…”
Section: Discussionmentioning
confidence: 99%